Appropriate Proportion of Water Meal (Wolffia arrhiza (L.)) and Commercial Diet in Combined Feeding for Tilapia Fingerlings Rearing - Sirirustananun, N. (International Journal of Agricultural Technology, 2018)
Studying the growth performance of tilapia fingerlings fed with different proportions of dried water meal and commercial diet was carried out. The experiment consisted of 4 treatments and 3 replications that produced in 0.15 m3 circle cement pond (50 fingerlings per unit). Fingerlings were fed commercial diet (CD) combined with dried water meal (DWM) at 100:0 (control treatment), 70:30, 50:50 and 30:70 for 75 days and the average initial weight of fish were 0.82±0.02 g, 0.85±0.05 g, 0.76±0.11 g and 0.74±0.04 g respectively which no significant difference (p>0.05). The results indicated that fish gradually grew throughout the experiment. The average weight gain, average daily growth and average specific growth rate of fish fed with 100:0 of CD and DWM showed significantly higher (p<0.05) than other treatments (10.54±1.15 g 0.14±0.01 g day-1 and 3.54±0.14 % day-1 respectively). In the parts of feed conversion ratio, fish were fed 100:0 of CD and DWM showed significantly lower (p<0.05) than other treatments (1.61±0.18) but no significant difference when compared with 70:30 of CD and DWM feeding (2.21±0.58). DWM might not be suitable for direct feeding however its adventage could make fat accumulation in fish body lower than fish fed with 100% of CD and revealed high protein level in their body. The combined feeding between CD and DWM at 70:30 could reduce feed cost about 12.60% and showed no contrast on feed conversion ratio when compared with 100% CD feeding that is the best choice for DWM utilization.